Intentional replantation as an alternative to dental implant: a 10-years follow-up case report - Dezan Junior, Eloi [UNESP]; Bueno, Carlos Roberto Emerenciano [UNESP]; Rosselli, Eliana Rodrigues; Cintra, Luciano Tavares Angelo [UNESP] (Dental Press International, 2019)
Objective: This case report shows a successful viable treatment for an endodontically treated permanent mandibular molar which presented clinical symptoms 6 months after the endodontic treatment. Since endodontic retreatment or paraendodontic surgery were not indicated, the chosen technique was intentional replantation. Case Report: One hour before the procedure, the patient rinsed his mouth with chlorhexidine gluconate 0.12%. The patient was prepared for surgery and profound inferior alveolar and lingual nerve block anesthesia was achieved with 2% mepivacaine containing 1/100,000 adrenaline. The procedure started with the least traumatic extraction as possible and immediately wrapping the extracted tooth in physiological saline-moistened gauze, while the roots were evaluated for vertical fractures, followed by apicoectomy. The cavities were retro-prepared with high-speed bur under irrigation with physiological saline and white mineral trioxide aggregate (MTA) was used for retrofilling. Immediately, the tooth was repositioned in the alveolus. Two 4-0 silk sutures were used to suture and stabilize the tooth. After one year, the patient returned for radiographic and clinical control, which revealed no more response to vertical percussion. After 10 years, the images show radiographic apical repair, without evidence of root resorption or periapical lesion. Conclusion: Clinical examination associated with the reported absence of pain and normal mobility confirmed the procedure’s success, indicating this treatment as a valid alternative when an implant is not viable. This technique may help restore an original tooth to function instead of replacing it with a prosthetic or a dental implant.
Keywords: Apicoectomy; Endodontics; Tooth apex; Tooth replantation